2017
DOI: 10.5500/wjt.v7.i1.98
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil toxicity mimicking acute cellular rejection in a small intestinal transplant

Abstract: Mycophenolate mofetil (MMF) is an important medication used for maintenance immunosuppression in solid organ transplants. A common gastrointestinal (GI) side effect of MMF is enterocolitis, which has been associated with multiple histological features. There is little data in the literature describing the histological effects of MMF in small intestinal transplant (SIT) recipients. We present a case of MMF toxicity in a SIT recipient, with histological changes in the donor ileum mimicking persistent acute cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…146,193 In intestinal transplantation, in the setting of MPA-associated gastrointestinal toxicities, azathioprine use has been reported in a case series with documented amelioration of gastrointestinal symptoms. 150 Its use was also described in a case series where azathioprine was used along with belatacept and prednisone as a rescue therapy in setting of tacrolimus associated kidney dysfunction. 194 Azathioprine has been associated with less GI side effects compared to MMF in heart transplant.…”
Section: Recommendation 8 Evidence Summary: Role Of Azathioprinementioning
confidence: 99%
See 3 more Smart Citations
“…146,193 In intestinal transplantation, in the setting of MPA-associated gastrointestinal toxicities, azathioprine use has been reported in a case series with documented amelioration of gastrointestinal symptoms. 150 Its use was also described in a case series where azathioprine was used along with belatacept and prednisone as a rescue therapy in setting of tacrolimus associated kidney dysfunction. 194 Azathioprine has been associated with less GI side effects compared to MMF in heart transplant.…”
Section: Recommendation 8 Evidence Summary: Role Of Azathioprinementioning
confidence: 99%
“…109,231,234,235 In intestinal transplantation, corticosteroids are a standard component of early-and long-term M-IMS regimens as illustrated by observational studies that persistently include them as essential components of M-IMS in this population. 51,52,[54][55][56][150][151][152][153]194,[243][244][245][246] In heart transplantation, most patients are either maintained on corticosteroids or withdrawal is attempted at 3-6 months or greater post-transplant. [247][248][249][250][251][252] At 1 and 5 years post-transplant, 89% and 52% of recipients, respectively, continued to be maintained on corticosteroids.…”
Section: Recommendation 9 Evidence Summary: Corticosteroid Withdrawalmentioning
confidence: 99%
See 2 more Smart Citations
“…Histological findings of intestinal rejection (Ruiz et al, 2004) are not specific and high apoptosis rates can be found in patients receiving mycophenolate mofetil (Apostolov et al, 2017) or during adenovirus infections (Kaufman et al, 2002). As the 5-gene set also identifies RX and IRX biopsies, it could be useful to discriminate those "false rejection" biopsies, avoiding the aggressive anti-rejection therapies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%